Involvement of VILIP-1 (visinin-like protein) and opposite roles of cyclic AMP and GMP signaling in in vitro cell migration of murine skin squamous cell carcinoma - Schönrath, Katharina (2010)
VILIP-1 (visinin-like protein 1) is downregulated in various human squamous cell carcinoma. In a mouse skin SCC model VILIP-1 expression is reduced in aggressive tumor cells, accompanied by reduced cAMP levels. Overexpression of VILIP-1 in aggressive SCC cells led to enhanced cAMP production, in turn causing a reduction in invasive properties. Moreover, in primary neurons and neuronal tumor lines VILIP-1 enhanced cGMP-signaling. Here, we set out to determine whether and how cAMP and cGMP-signaling contribute to the VILIP-1 effect on enhanced SCC model cell migration, and thus most likely invasiveness in vivo. We found stronger increase in cGMP levels in aggressive, VILIP-1-negative SCC cells following stimulation of guanylyl cyclases NPR-A and -B with the natriuretic peptides ANP and CNP, respectively. Incubation with ANP or 8Br-cGMP to increase cGMP levels further enhanced the migration capacity of aggressive cells, whereas cell adhesion was unaffected. Increased cGMP was caused by elevated expression levels of NPR-A and NPR-B. However, the expression level of VILIP-1 did not affect cGMP signaling and guanylyl cyclase expression in SCC. In contrast, VILIP-1 led to reduced migration of aggressive SCC cells depending on cAMP levels as shown by use of adenylyl cyclase inhibitor 2′,3′-dideoxyadenosine. Involvement of cAMP-effectors PKA and EPAC play a role downstream of adenylyl cyclase activation. VILIP-1-positive and -negative cells did not differ in mRNA expression of adenylyl cyclases, but an effect on enhanced protein expression and membrane localization of ACs was shown to underlie enhancement of cAMP production and, thus, reduction in cell migration by VILIP-1.